Huetar Etymology of the Word Toboba ‘Venomous Snake’ - Portilla, Mario (2021)
In this paper, the author proposes a Huetar origin for the word toboba ‘poisonous snake’. This Chibchan language was the most important substrate language of Costa Rican Spanish. First of all, he analyses the semasiology of this lexeme and its geographical spread. Then, using the Comparative Method, he establishes a series of systematic correspondences between this word and possible cognates of other related languages in order to prove their kinship and origin from the same reconstructed protoform.